The role of Institutional quality, human capital development on economic growth in Sub-Saharan Africa - Lawal Olamilekan Abdulwahab (International Journal of Business Economics (IJBE), 2023)
Purpose –  The paper examined the role of institutional quality and human capital development on economic growth in Sub-Saharan African (47) countries.Methodology –The study employed secondary data from all the countries within the Sub-Saharan African countries region for the period of nineteen years, with the exclusion of South Sudan due to insufficient data; all the data was sourced from the World Bank Database and was analyzed via the use of fixed effects regression based on the nature of the study (i.e., Panel data).Findings –This study's findings revealed that IQ and HDI are statistically insignificant in the economic growth of the SSA region.Originality/Novelty – The study covered the existing gaps by adequately and sufficiently measuring the institutional quality and human capital index's role on the stated region's economic growth.Implications -–The study, therefore, recommends that various authorities should enhance both health and educational systems, allocating adequate resources to both sectors to foster economic growth, and there should be proper monitoring and evaluation measures to curtail the corruption and insecurity within this region.